Do the Historical Biogeography and Evolutionary History of the Digenean Margotrema spp. across Central Mexico Mirror Those of Their Freshwater Fish Hosts (Goodeinae)? - Martínez Aquino, Andrés (2014)
Host-parasite systems provide an ideal platform to study evolution at different levels, including codivergence in a historical biogeography context. In this study we aim to describe biogeographic and codivergent patterns and associated processes of the Goodeinae freshwater fish and their digenean parasite (Margotrema spp.) over the last 6.5 Ma (million years), identifying the main factors (host and/or hydrogeomorphology) that influenced the evolution of Margotrema. We obtained a species tree for Margotrema spp. using DNA sequence data from mitochondrial and nuclear molecular markers (COI and ITS1, respectively) and performed molecular dating to discern divergence events within the genus. The dispersal-extinction-cladogenesis (DEC) model was used to describe the historical biogeography of digeneans and applied to cophylogenetic analyses of Margotrema and their goodeine hosts. Our results showed that the evolutionary history of Margotrema has been shaped in close association with its geographic context, especially with the geological history of central Mexico during the Pleistocene. Host-specificity has been established at three levels of historical association: a) Species-Species, represented by Xenotaenia resolanae -M. resolanae exclusively found in the Cuzalapa River Basin; b) Species-Lineage, represented by Characodon audax-M. bravoae Lineage II, exclusive to the Upper and Middle Mezquital River Basin, and c) Tribe-Lineage, including two instances of historical associations among parasites and hosts at the taxonomical level of tribe, one represented by Ilyodontini-M. bravoae Lineage I (distributed across the Ayuquila and Balsas River Basins), and another comprised of Girardinichthyini/Chapalichthyini-M. bravoae Lineage III, found only in the Lerma River Basin. We show that the evolutionary history of the parasites is, on several occasions, in agreement with the phylogenetic and biogeographic history of their hosts. A series of biogeographic and host-parasite events explain the codivergence patterns observed, in which cospeciation and colonisation via host-switching and vicariant plus dispersal events are appreciated, at different times during the diversification history of both associates, particularly during the Pleistocene.